Surface modification of silicone tubes by functional carboxyl and amine, but not peroxide groups followed by collagen immobilization improves endothelial cell stability and functionality. (2nd March 2015) - Salehi-Nik, Nasim; Amoabediny, Ghassem; Shokrgozar, Mohammad Ali; Mottaghy, Khosrow; Klein-Nulend, Jenneke; Zandieh-Doulabi, Behrouz
Abstract: Surface modification by functional groups promotes endothelialization in biohybrid artificial lungs, but whether it affects endothelial cell stability under fluid shear stress, and the release of anti-thrombotic factors, e.g. nitric oxide (NO), is unknown. We aimed to test whether surface-modified silicone tubes containing different functional groups, but similar wettability, improve collagen immobilization, endothelialization, cell stability and cell-mediated NO-release. Peroxide, carboxyl, and amine-groups increased collagen immobilization (41–76%). Only amine-groups increased ultimate tensile strength (2-fold). Peroxide and amine enhanced (1.5–2.5 fold), but carboxyl-groups decreased (2.9-fold) endothelial cell number after 6 d. After collagen immobilization, cell numbers were enhanced by all group-modifications (2.8–3.8 fold). Cells were stable under 1 h-fluid shear stress on amine, but not carboxyl or peroxide-group-modified silicone (>50% cell detachment), while cells were also stable on carboxyl-group-modified silicone with immobilized collagen. NO-release was increased by peroxide and amine (1.1–1.7 fold), but decreased by carboxyl-group-modification (9.8-fold), while it increased by all group-modifications after collagen immobilization (1.8–2.8 fold). Only the amine-group-modification changed silicone stiffness and transparency. In conclusion, silicone-surface modification of blood-contacting parts of artificial lungs with carboxyl and amine, but not peroxide-groups followed by collagen immobilization allows the formation of a stable functional endothelial cell layer. Amine-group-modification seems undesirable since it affected silicone's physical properties.